Упростите вырожение:а — 3а — 7 — 2а3а — 5х — 2х + 4 — 2х1 + х2с Зс + 4 — Зс 2с + 1За 2а — 1 — 2а 4 + За

упростите вырожение:

(а - 3)(а - 7) - 2а(3а - 5)

(х - 2)(х + 4) - 2х(1 + х)

2с (Зс + 4) - Зс (2с + 1)

За (2а - 1) - 2а (4 + За)

     

    2.x^2+4x-2x-8-2x-2x^2=-x^2-8

    3.6c^2+8c-6c^2-3c=5c

  • 1. a^2-7a-3a+21-6a^2+10a=-7a^2+21

    2с (Зс + 4) - Зс (2с + 1)=6c^2+8c-6c^2-3c=5c

  • (а - 3)(а - 7) - 2а(3а - 5)=a^2-10a+21-6a^2+10a=-5a^2+21

    За (2а - 1) - 2а (4 + За)=6a^2-3a-8a-6a^2=-11a

  •  

    (х - 2)(х + 4) - 2х(1 + х)=x^2+2x-8-2x-2x^2=-x^2-8

     

    4.6a^2-3a-8a-6a^2=-11a